1995
DOI: 10.1071/wr9950359
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Nocturnal Forest Birds and Mammals in North-Eastern New South Wales: Relationships With Environmental Variables and Management History.

Abstract: A regional survey of the forests in north-eastern New South Wales recorded eight species of nocturnal forest birds and nine species of arboreal marsupials from 291 sites. Three major environmental gradients accounting for the distribution of these species in north-eastern New South Wales were identified: elevation, forest type (wet forest types having a dense mesic understorey or dry forest types having an open or sparse understorey), and logging intensity. Characteristic assemblages of species were associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 28 publications
3
42
1
Order By: Relevance
“…hollow abundance) for arboreal mammals in relation to disturbance regimes. Arboreal marsupials occurring in these forests include the Greater Glider Petauroides volans; Kavanagh et al, 1995;Eyre, 2006) which is a major prey species for threatened forest owl species (Kavanagh, 1988) and the threatened Spotted-tailed Quoll Dasyurus maculatus; Glen and Dickman, 2006), as well as threatened arboreal marsupial species such as the Yellow-bellied Glider Petaurus australis; Kavanagh et al, 1995). While habitat availability, including tree hollows, is crucial for these animals (Goldingay, 2012), disturbance regimes will also have direct effects on these species through processes which affect animal mortality and the capacity for animals to reproduce successfully.…”
Section: Discussionmentioning
confidence: 99%
“…hollow abundance) for arboreal mammals in relation to disturbance regimes. Arboreal marsupials occurring in these forests include the Greater Glider Petauroides volans; Kavanagh et al, 1995;Eyre, 2006) which is a major prey species for threatened forest owl species (Kavanagh, 1988) and the threatened Spotted-tailed Quoll Dasyurus maculatus; Glen and Dickman, 2006), as well as threatened arboreal marsupial species such as the Yellow-bellied Glider Petaurus australis; Kavanagh et al, 1995). While habitat availability, including tree hollows, is crucial for these animals (Goldingay, 2012), disturbance regimes will also have direct effects on these species through processes which affect animal mortality and the capacity for animals to reproduce successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Kavanagh et al (1995) reported a positive correlation between koala occurrence and high intensity logging in the forests of north-east NSW based on regional scale surveys. This result needs to be interpreted with caution.…”
Section: Impacts Of Forestrymentioning
confidence: 99%
“…This result needs to be interpreted with caution. Firstly Kavanagh et al (1995) classified forests with a history of several logging cycles and few or no old trees with hollows as intensively logged, while we have classified forests with the same history in Pine Creek as selectively logged or logged at low to moderate intensity. A long history of logging does not necessarily equate with high logging intensity.…”
Section: Impacts Of Forestrymentioning
confidence: 99%
“…For example, while clearfelling will remove habitat, koalas may persist in selectively-logged forests (Kavanagh et al 1995;Kavanagh et al 2007). Thus the level of threat posed by logging is situation-specific and is determined by the appropriateness of the management regime, and adherence to its prescriptions.…”
Section: Habit Loss Fragmentation And/or Degradationmentioning
confidence: 99%